Information Asymmetry, Deferred Tax Burden, Bonus Compensation and Leverage on Profit Management in Manufacturing Companies in the Goods and Consumer Industry Sector: Asimetri Informasi, Beban Pajak Tangguhan, Kompensasi Bonus dan Leverage Terhadap Manajemen Laba pada Perusahaan Manufaktur Sektor Industri Barang dan Konsumsi - Lukmana, Amelia; Sriyono, Sriyono (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to examine the effecct of Information Asymmetry, Deferred Tax Expense, Bonus Compensation, and leverage on earning management. The approach used in the research is a quantitative approach. The population in this study is manufacturing companies in the goods and consumption industrial sector listed on the Indonesia Stock Exchange. The sample in study was 108 companies listed on the Indonesia Stock Exchange in 2018-2020. The data used in the study is secondary data taken from the Indonesia Stock Exchange. Analysis of the data used in this study is Eviews version 9 with the aim of testing Information Asymmetry (X1), Deferred Tax Expense (X2), Bonus Compensation (X3), Leverage (X4), on Earning Management (Y). The result of this study indicate that simultaneously there is a significant effect between Information Asymmetry, Deferred Tax Expense, Bonus Compensation, and leverage on Earning Management. While partially Deferred Tax Expense have a significant Positive effect on Earning Management. Information Asymmetry, Bonus Compensation, and leverage does not have a significant effect on Earning Management.